THE CONTENT AND TASKS OF INTRODUCING PRESCHOOL CHILDREN TO THE BASICS OF A HEALTHY LIFESTYLE (American Journal of Pedagogical and Educational Research, 2023)
This article describes the content and tasks of introducing preschool children to the basics of a healthy lifestyle, taking into account the individual characteristics of the child, and the content of cooperation between educators and parents in organizing a healthy lifestyle.